Talking about an emergency in an urgent situation: prosody and information - Charlotte Danino (Anglophonia)
This paper deals with the role of prosody as a semantic component in media speech. Based on CNN’s live broadcast on 9/11, linguistic productions are analyzed as spontaneous but heavily constrained speech since the breaking news format and both the temporal and cognitive pressures shape the ensuing utterances about this still ongoing event. The article starts by presenting the breaking news format and the type of interaction. It proceeds to analyze data from a sociodiscursive point of view in order to consider prosody first as a semantic-pragmatic pattern, then as pivotal tool for participants’ alignment in interaction. Finally, the examination of pauses in spontaneous pressured speech gives new insight into the sense of emergency emerging from the corpus. These analyses lead us to reconsider the role of prosody in information structuring and to consider that it might have more to do with information processing.